Delivering project SCORE in competitive youth sport settings - Ferreira, M.; Santos, F.; Fernández-Villarino, M. A.; Mergler, J.; Strachan, L.; MacDonald, D. J. (Frontiers in Sports and Active Living, 2024)
Introduction This study evaluates the effectiveness of the Project SCORE intervention in fostering Positive Youth Development (PYD) within competitive youth sport settings in Portugal. Project SCORE is an online PYD-focused tool developed to assist coaches in promoting the 4Cs—competence, confidence, connection, and character—within their coaching.